Attitude Toward Mathematics of Future Teachers: How Important Are Creativity and Cognitive Flexibility? - de-la-Peña, Cristina; Fernádez-Cézar, Raquel; Solano-Pinto, Natalia (Frontiers in Psychology, 2021)
The attitude towards mathematics is shaped by cognitive components such as beliefs and cognitive processes. However, the importance of cognitive processes in attitude towards mathematics has not yet been researched. Therefore, the aim of this study was to identify the role of cognitive processes, creativity and cognitive flexibility, in the attitude towards mathematics of future teachers. For that purpose, 218 university students, preservice teachers, completed assignments on creativity and cognitive flexibility and a questionnaire on attitude towards mathematics. The results showed that the use of innovative details (a creativity subscale) rises the probability of exhibiting a positive attitude towards mathematics by 1.81. Besides, the cognitive flexibility rises this probability by 2.32. The conclusion is that both, details and cognitive flexibility act as good predictors of positive attitude towards mathematics. This has implications for educational practice in the planning of mathematics instruction in higher education, specifically, in future teachers.